A Closer Look at the Genomic Variation of Geographically Diverse Mycobacterium abscessus Clones That Cause Human Infection and Disease - Davidson, Rebecca M. (Frontiers in Microbiology, 2018)
Mycobacterium abscessus is a multidrug resistant bacterium that causes pulmonary and extrapulmonary disease. The reported prevalence of pulmonary M. abscessus infections appears to be increasing in the United States (US) and around the world. In the last five years, multiple studies have utilized whole genome sequencing to investigate the genetic epidemiology of two clinically relevant subspecies, M. abscessus subsp. abscessus (MAB) and M. abscessus subsp. massiliense (MMAS). Phylogenomic comparisons of clinical isolates revealed that substantial proportions of patients have MAB and MMAS isolates that belong to genetically similar clusters also known as ‘dominant clones’. Unlike the genetic lineages of Mycobacterium tuberculosis that tend to be geographically clustered, the MAB and MMAS clones have been found in clinical populations from the US, Europe, Australia and South America. Moreover, the clones have been associated with worse clinical outcomes and show increased pathogenicity in macrophage and mouse models. While some have suggested that they may have spread locally and then globally through ‘indirect transmission’ within cystic fibrosis (CF) clinics, isolates of these clones have also been associated with sporadic pulmonary infections in non-CF patients and unrelated hospital-acquired soft tissue infections. M. abscessus has long been thought to be acquired from the environment, but the prevalence, exposure risk and environmental reservoirs of the dominant clones are currently not known. This review summarizes the genomic studies of M. abscessus and synthesizes the current knowledge surrounding the geographically diverse dominant clones identified from patient samples. Furthermore, it discusses the limitations of core genome comparisons for studying these genetically similar isolates and explores the breadth of accessory genome variation that has been observed to date. The combination of both core and accessory genome variation among these isolates may be the key to elucidating the origin, spread and evolution of these frequent genotypes.